Есть ли прок для партий от манипуляций с избирательной системой? Положение о выборах и избирательная инженерия в Польше (1989–1993) - Каминьский, М. (Социология: теория, методы, маркетинг, 2005)
Electoral reforms had profound political consequences for postcommunist Poland. The majority system promoted the fall of communism, while later changes to the electoral law helped the former communists to reclaim power. Despite the play for high stakes and top priority given to electoral design by political actors, their manipulative efforts were hardly rewarded. Although the political parties were ex ante seat maximizers, they supported the electoral law that ex post would have given them the most seats about as frequently as they supported the closest competitor of the above mentioned one. The reasons for their miscalculations included a lack of methodological expertise, unexpected shifts in voter preferences, transitionspecific poll biases, as well as new entrants and coalitions that emerged in the period between the introduction of the new electoral law and elections. No significant differences among the various kinds of parties were found. The results do show that the effectiveness of manipulation has strongly increased over time.